Everything sad is untrue : (a true story) - Nayeri, Daniel (Levine Querido, 2020)
"At the front of a middle school classroom in Oklahoma, a boy named Khosrou (whom everyone calls 'Daniel') stands, trying to tell a story. His story. But no one believes a word he says. To them he is a dark-skinned, hairy-armed boy with a big butt whose lunch smells funny; who makes things up and talks about poop too much. But Khosrou's stories, stretching back years, and decades, and centuries, are beautiful, and terrifying, from the moment he, his mother, and sister fled Iran in the middle of the night, stretching all the way back to family tales set in the jasmine-scented city of Isfahan, the palaces of semi-ancient kings, and even the land of stories"--Jacket flap.